Enhanced oral bioavailability of fluvastatin by using nanosuspensions containing cyclodextrin - Li J; Yang M; Xu WR (Dove Medical Press, 2018)
Li Jun,1,2,* Yang Min,2,* Xu Wen-Rong11School of Medical Science and Laboratory Medicine, Jiangsu University, Zhenjiang, Jiangsu 212013, China; 2Department of Intensive Care Unit, Chest Hospital Affiliated to Shanghai Jiaotong University, Shanghai 200030, China*These authors contributed equally to this workBackground: In this study, fluvastatin (FVT) nanosuspensions containing cyclodextrin were developed to improve oral bioavailability.Methods: FVT nanosuspensions containing cyclodextrin were prepared by a high pressure homogenization technique. The nanosuspensions system was then characterized by transmission electron microscopy (TEM), particle size, differential scanning calorimetry (DSC) and powder X-ray diffractometry (PXRD). In addition, in vitro drug release properties, pharmacokinetics and pharmacodynamics were also investigated in detail.Results: After lyophilization, the nanosuspensions could be redispersed gently and with a narrow particle size distribution, but the particle size has no obvious change. The powder X-ray diffraction and differential scanning calorimetry of FVT nanosuspensions showed that FVT existed in amorphous form in nanosuspensions. In vitro release, FVT nanosuspensions have sustained-release properties. Meanwhile, FVT nanosuspensions could significantly modify the pharmacokinetic profile and increase the bioavailability of FVT by more than 2.4-fold in comparison with the FVT capsules group. In vivo irritation test showed that there was almost no evidence of hemorrhagic mucosal erosion and intestinal villus destruction in rat gastric mucosa.Conclusion: The combination of nanocrystallization and cyclodextrin complexation techniques is a new attempt to formulate poorly water-soluble FVT. Keywords: fluvastatin, HP-β-CD, nanosuspensions, bioavailability, irritation test